LARYNX PATHOLOGY AT PATIENTS WITH GASTROINTESTINAL TRACT DISORDERS - Yerkenovna, Toguzbaeva Dinara (European Scientific Journal, ESJ, 2013)
The conducted clinical and instrumental study revealed that the aggregate group of the patients with chronic diseases of throat differs by increased frequency of isolated and combined disorders of gastrointestinal tract. If a patient has such symptoms as hoarseness, tickling, scratching, burning, feeling of dryness in throat, frequent variant of gastro-intestinal tract disorders is gastroesophageal reflux disease with pharyngolaryneal reflux. There are such severe pathologies of throat as pachydermia of vocal cords and nodules of vocal cords among more frequently met disorders at gastro-intestinal tract diseases. High probability of accompanied pathology of throat in the form of pachydermia and nodules of vocal cords at patients with gastro-intestinal tract disorders stipulates for the necessity of conducting fibrorhynolaryngoscopy in combination with fibergastroscopy.